2019
DOI: 10.7592/ejhr2019.7.2.cendra
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotypes depicted in online sexist jokes

Abstract: This research aimed to explore gender stereotypes depicted in online sexist jokes collected from laughfactory.com. Linguistically speaking, jokes as a subtype of humour have become a common phenomenon in our everyday lives. Unfortunately, not all jokes can bring positive vibes for everyone. Yet, these forms of jokes are still commonly found, especially on the Internet. Some online sources, including websites of jokes, present a lot of collections of jokes for fun, but a number of the jokes are categorized as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…By focusing on how Nigerian stand-up comedians pursue and instantiate concepts in their jokes, the paper has shown that analyzing gender stereotyping in jokes does not necessarily need to include focusing on the targets of the jokes as shown in some studies (e.g. Cendra et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on how Nigerian stand-up comedians pursue and instantiate concepts in their jokes, the paper has shown that analyzing gender stereotyping in jokes does not necessarily need to include focusing on the targets of the jokes as shown in some studies (e.g. Cendra et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil temuan dilapangan telah menunjukkan bahwa bias gender saat ini menjadi permasalahan dasar terhadap segala aspek. Permasalahan bias gender yang marak terjadi tidak hanya pada kehidupan bermasyarakat (Cendra et al, 2019). World Economic Forum (WEF) dan Gender Inequality Index (GII) tahun 2019 mengemukakan Gap/ketimpangan gender di Indonesia dengan skor 0,48 poin dan terkategori tinggi di kawasan ASEAN.…”
Section: Pendahuluanunclassified
“…Disparagement humour research suggests that although no longer politically correct, some stereotypes are still "fair game" as long as they are the subject of humorous content (Cendra et al 2019;Lockyer & Pickering 2008). However, limited research has studied whether humour decreases, increases, or has no effect on prejudiced attitudes (Goodwin & Whannel 1990).…”
Section: Disparagement Humour Researchmentioning
confidence: 99%